Des interventions en français réinvesties dans la résolution de problèmes en mathématiques au primaire : Vers le développement d’un contrôle interdisciplinaire chez les élèves - Saboya, Mireille; Tremblay, Mélanie (Canadian Journal of Education/Revue canadienne de l'éducation, 2021)
Problem solving is central in teaching and learning mathematics. In two collaborative research projects we co-construct interventions aimed to develop student's mathematical control. Teachers play a fundamental role to help their students to reflect on their actions. These projects take place at the primary level. The first one took place in special education classes, 2nd and 3rd grades. The second one is in 5th and 6th grades. The analysis of class sessions in mathematics and teacher meetings helped determine the influence of the activities carried out in the teaching of French. This text presents somes interventions and discusses their potential to help students to develop a mathematical control activity. Our results enrich interdisciplinary research that focuses on mathematics and french courses.